Critical Religion Takes a Punch: Notes on a Scholarly Skirmish - Goldenberg, Naomi R. (Method & theory in the study of religion, 2024)
In this reply to the article “Can Critical Religion Play by Its Own Rules? Why There Must Be More Ways to Be ‘Critical’ in the Study of Religion” by Galen Watts and Sharday Mosurinjohn (2022), I take exception to the authors’ criticisms. I call attention to Watts’ and Mosurinjohn’s implication that critical religion enables racism, their imaginary construction of a methodological ‘school’ with rigid ‘rules,’ and their simplistic dismissal of Foucault’s approach to discourse analysis. I then suggest that the suspension of reified categories in Religious Studies opens up promising avenues for theory and research.